E-learning e strategie inclusive: uno studio per rilevare le opinioni dei docenti dell'Università Roma Tre. - Barbara De Angelis (LED Edizioni Universitarie, 2020)
This contribution addresses aspects of the reflection on e-learning for higher education, with the purpose of outlining some operational considerations related to the presence of technologically mediated practices within university's educational contexts. The culture of functioning in enabling contexts and the principle of accessibility as a cornerstone of inclusive teaching were the two perspectives considered here and applied to focus the implementation of inclusive e-learning, and to assess its usability and sustainability from an educational and methodological point of view. It is intended to highlight how fundamental, in the educational planning phase, the function of the teacher who consciously chooses the use of educational tools and devices. The study in question intends to explore, through the administration of a specific questionnaire, the opinions of university teachers in relation to the design and organization in an inclusive sense of their e-learning training offer in the university context. An investigation of this type may also encourage the launch of further studies on the philosophy of Universal Design to be deepened within higher education in our country, according to practices already present at an international level.